Esteban Cristiani: un compositor italiano entre España e Hispanoamérica - Domínguez, José María (Cuadernos de Música Iberoamericana, 2018)
This is the first reconstruction of the biography and stage-music output of the Italian composer Esteban Cristiani (c. 1770–c. 1829), who lived and worked in Spain (Barcelona, Madrid, Seville) from 1802 and subsequently in Cuba and Mexico. The article focuses on the time he spent in Madrid (1803-c. 1815), as this is his best-known and most documented period. The methodological approach used to appraise the operas premiered in Madrid in the midst of the controversy surrounding the theatre, consists of the analysis of his most successful work, Ramona y Roselio, and Cristiani’s repercussion in the press of the period. An annotated catalogue of all of Cristiani’s works located to date is also included.